Estudos morfológicos e anatômicos em euterpe oleracea mart. (açaí preto) e euterpe sp. (açaí branco e espada). - Mesquita, Sandro Antonio J. (Museu Paraense Emílio Goeldi, 2022)
The açaizeiro (Euterpe oleracea Mart.) is a regional species of food and economic importance in the Amazon estuary floodplains. Current research on the species has focused primarily on ecology and management. However, morphological and anatomical studies are necessary to support comparisons between varieties or types existing in the genus. The objective of this research is to perform morphological and anatomical studies on E. oleracea Mart. (black acai) and Euterpe sp (white and sword acai) for further comparison. The botanical material was collected on Ilha do Combu, municipality of Acará (PA) and evaluated morphologically by measurements of leaves, inflorescences and infructescences and anatomically by freehand histological sections of adult leaf structures for each species. The morphological results differed in leaf variations for black açaí, inflorescences in sword açaí and infructescences in white açaí; as for the anatomical structures similarities were observed in the epidermis, tetracyclic stomata and the presence of hypodenne, lacunar parenchyma formed by 4 to 5 layers of cells and between the cells the presence of bundles. The main anatomical difference was observed in the palisade parenchyma, which is uniseriate in black and sword açaí and biseriate in white açaí.